Types and Functions of Sarcasm in Indonesian Political Conversation on ‘X’ - Putri, Saskia Aliyah; Sabila, Syaufah; Suka, Mariska Adinda br. Ginting; Hasibuan, Fitri (Universitas Pamulang, 2026)
This study investigates how sarcasm is produced and functions within Indonesian political conversations on X (formerly Twitter). Although previous research has examined sarcasm in entertainment, religion, and media contexts, studies focusing on political discourse especially within Indonesia’s highly polarized digital environment remain limited. This gap indicates the need to understand not only the types of sarcasm used but also their rhetorical purposes in online political interactions. Therefore, the aim of this study is to classify the forms of sarcasm using Camp’s (2011) framework and to reveal how each type functions as a tool for political criticism, identity building, and ideological positioning. Adopting a qualitative descriptive design, this research analyzes 30 sarcastic posts and replies responding to government-related issues on X. The instrument consists of an analytical rubric based on linguistic cues of sarcasm, while the data were collected through purposive sampling of public posts from September to October 2025. The data were processed through transcription, classification, and interpretive analysis. The findings show that propositional and illocutionary sarcasm dominate, indicating a strong preference for indirect yet sharp political critique. Sarcasm also serves as a rhetorical strategy for expressing resistance, mocking authority, and strengthening group affiliation among users. These findings imply that sarcasm is not merely humor in digital communication but a significant form of civic engagement and political meaning-making in Indonesia’s online public sphere.